Linkage between Foreign Direct Investment, Domestic Investment and Economic Growth: Evidence from Nigeria - GüngÃ¶r, Hasan; Ringim, Salim Hamza (International Journal of Economics and Financial Issues, 2017)
Foreign direct investment (FDI) in the words of Rutherford (1992) spurs economic growth in less developed countries; which is in alignment with the modernization theory. However, the dependency theorist contends that dependence on foreign investment is expected to affect growth and income distribution negatively. It on this premise, that this study is conducted base on this argument to empirically analyze the linkage between foreign direct investment, domestic investment and economic growth for the case of Nigeria. To this end, annual time series data for the period of 1980 to 2015 was employed. The study employs Johansen multivariate cointegration test and Vector Error Correction model (VECM) as estimation techniques. The Johansen cointegration result of the study reveals that, foreign direct investment (FDI) domestic investment (DI) and economic growth have a long-run equilibrium relationship. According to the VECM result and the speed of adjustment of the variables towards their long-run equilibrium path was 52.55%. Furthermore, Granger Causality test reveals a uni-directional causality running from FDI to economic growth that is, FDI is an important predictor of economic growth. This goes to validate the FDI lead growth hypothesis for Nigeria. Keywords: Foreign Direct Investment (FDI), Domestic Investment (DI), Economic growth, Nigeria, Time series, Vector error correction model (VECM) JEL Classifications: F3, F43, C22